2019
DOI: 10.37358/rc.19.4.7121
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Near-Infrared (780nm) Light Transillumination Accuracy for Detection of Incipient Caries Lesions

Abstract: The aim of study was to evaluate the accuracy of the near-infrared light transillumination technique used in the detection of the proximal incipient dental caries. The study was performed on 12 medium caries risk subjects (mean age of 26.5). A total number of 312 proximal dental surfaces from the posterior dental group were included in the study. All the proximal surfaces, which had not been restored, or unaffected by cavitated dental caries, were assessed by a near-infrared transillumination camera system usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…These findings are consistent with an X-ray microtomography study by Huang et al (2007), which showed significantly lower mineral density in WSLs compared to sound enamel [24]. Another study by Topoliceanu et al (2013) also found a reduction in Ca and phosphorous ions in white and brown spot lesions relative to sound enamel in molar teeth [14].…”
supporting
confidence: 88%
See 1 more Smart Citation
“…These findings are consistent with an X-ray microtomography study by Huang et al (2007), which showed significantly lower mineral density in WSLs compared to sound enamel [24]. Another study by Topoliceanu et al (2013) also found a reduction in Ca and phosphorous ions in white and brown spot lesions relative to sound enamel in molar teeth [14].…”
supporting
confidence: 88%
“…Recent studies have demonstrated significant mineral loss in white spot lesions in comparison to normal human enamel. Examination of the occlusal surface of enamel using SEM combined with EDS has revealed a significant paucity of calcium, phosphorus, and oxygen ions in early carious lesions relative to sound enamel [14]. However, the characteristics of pit-and-fissure caries may differ from those of smooth surface caries, which are more frequently encountered in orthodontic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Oral pathology can lead to improper nutritional status, by pain and discomfort related to dental caries, periodontal disease and ill-fitted fixed dentures or removable dentures [17][18][19][20][21][22][23]. Also, even treated with removable dentures, the extended partial edentation or total edentation affect severely the digestive function and the nutritional status [24,25].…”
Section: Resultsmentioning
confidence: 99%